2018
DOI: 10.1111/ajo.12848
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transabdominal cerclage in pregnancy: A single centre experience

Abstract: Laparoscopic transabdominal cerclage is a safe and effective procedure in women with poor obstetric histories. It requires the correct skill, expertise and patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In pregnant women, the mean time of surgery was 59 min. These data are comparable to those published by Gremeau et al [17] (average of 54 min) in nonpregnant women and Ades et al [18] (mean operation time of 57.5 min) in pregnant women . The rather similar operation times in pregnant and nonpregnant women in our cohort can be attributed to the fact that no additional procedures were required in pregnant women.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In pregnant women, the mean time of surgery was 59 min. These data are comparable to those published by Gremeau et al [17] (average of 54 min) in nonpregnant women and Ades et al [18] (mean operation time of 57.5 min) in pregnant women . The rather similar operation times in pregnant and nonpregnant women in our cohort can be attributed to the fact that no additional procedures were required in pregnant women.…”
Section: Discussionsupporting
confidence: 91%
“…Neonatal survival rates were overall satisfactory and ranged from 79 to 100% [17,24]. Mean GA at delivery was between 32.9 and 37.8 weeks [15,[17][18][19]25]. The mean GA at delivery in our patients was 34 + 4 weeks.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The laparoscopic approach is nowadays preferred by well-trained surgeons due to the advantages of shorter recovery times and hospital stays and less postoperative pain and adhesion formation than the open method. A study by Ades et al of laparoscopic transabdominal cerclage during pregnancy reported that all 19 patients enrolled in this study had no operative complications and were discharged within one day [20].…”
Section: Discussionmentioning
confidence: 61%
“…It is of vital importance for surgeons and patients to select the proper time of the cerclage placement and removal. Although the subject of whether LTCC should be performed during pregnancy remains controversial [12,15,36], there were no adverse events in all 3 pregnant participants with MLTCC-TR. To avoid the adverse effects (larger uterus, more abundant blood supply, higher risks of miscarriages) of the surgery during pregnancy [37], it was advised that our new approach be followed in nonpregnancy or first-trimester pregnancy.…”
Section: Discussionmentioning
confidence: 89%